Couplelinks online intervention for young couples facing breast cancer: A randomised controlled trial. Issue 3 (2nd November 2021) - Fergus, Karen; Ahmad, Saunia; Gardner, Sandra; Ianakieva, Iana; McLeod, Deborah; Stephen, Joanne; Carter, Wendy; Periera, Amanda; Warner, Ellen; Panchaud, Jim
Abstract: Objective: Young women with breast cancer and their partners are more distressed than couples who are affected later in life. While dyadic interventions in the context of cancer are promising, there are access barriers, particularly for younger couples. This study evaluated Couplelinks, a professionally facilitated,  web‐based program designed to help couples improve their conjoint coping. Method: This randomised controlled trial employed a waitlist control evaluation of the program. Outcomes included dyadic coping, relationship adjustment, depression, and anxiety. Results: Seventy‐five couples consented to participate and were randomised. The final analysis included 31 couples in the treatment group and 36 couples in the waitlist group. Modest improvements were found in positive dyadic coping but effects were not maintained at 3‐month follow‐up. No effect was seen on overall relationship adjustment. Conclusions: Our findings inform the rapidly expanding field of online programming for couples in general, and those affected by BC in particular. Intervention timing, 'dose', low overall relational distress, and the mainly enrichment rather than problem‐focus of Couplelinks may help explain the lack of change on relationship adjustment.